Large N-ightmare dark matter. Issue 5 (20th May 2021) - Morrison, Logan; Profumo, Stefano; Robinson, Dean J.
Abstract: A dark QCD sector is a relatively minimal extension of the Standard Model (SM) that admits Dark Matter (DM) candidates, but requires no portal to the visible sector beyond gravitational interactions: a "nightmare scenario" for DM detection. We consider a secluded dark sector containing a single flavor of light, vector-like dark quark gauged under (N). In the large-N limit, this single-flavor theory becomes highly predictive, generating two DM candidates whose masses and dynamics are described by few parameters: a light quark-antiquark bound state, the dark analog of the η' meson, and a heavy bound state of N quarks, the dark analog of the Δ ++ baryon. We show that the latter may freeze-in with an abundance independent of the confinement scale, forming DM-like relics for N ≲ 10, while the former may generate DM via cannibalization and freeze-out. We study the interplay of this two-component DM system, and determine the characteristic ranges of the confinement scale, dark-visible sector temperature ratio, and N that admit non-excluded DM, once effects of self-interaction constraints and bounds on effective degrees of freedom at the BBN and CMB epochs are included.